Materializing the Bible: scripture, sensation, place - Bielo, James S. (Bloomsbury studies in material religion, 2021)
Introduction: the sensory imperative -- Part 1. Variations on replication. 1.1:1 ; 2. Miniaturizing ; 3. Replicating replicas ; 4. Imagineering replicas ; 5. Re-enacting ; 6. Approximating ; 7. Filling intertextual gaps -- Part 2: Nature endowed. 8. Flower, Tree, herb ; 9. Trusting flora ; 10. Ingesting the word ; 11. Fauna ; 12. Stone, dirt -- Part 3. Choreographing experience. 13. When prayers become things ; 14. Publicity ; 15. Guiding ; 16. In place, in motion ; 17. Interactivity ; 18. Aural annotation ; 19. Textual annotation ; 20. Location coda: the sensory imperative (reprise) -- Appendix: Guide to materializing the Bible attractions.